Community Empowerment Through Fish Farming Household Scale As An Effort To Increase Animal Protein Consumption - Ima Kusumanti; Tin Herawati (International Journal Of Community Service, 2023)
Family food security can be obtained from the environment closest to where we live, namely by using the right method, one of which is through cultivating fish on limited land or better known as cultivating fish in buckets (budikdamber). This simple cultivation technique is carried out with the concept of planting fish and plants in the same container. So that the results from budikdamber can be the best alternative in meeting the needs of vegetable protein and animal protein in Situgede Village, Bogor-West Java, especially during the Covid-19 pandemic. In addition to meeting protein needs, this activity aims to be an alternative to creating jobs, if done with a good cropping pattern. So that fish and cultivated plants can be continuously obtained to meet consumer demand. As a result of the activities carried out, the Budikdamber activity is very good for the community in Situgede Village to continue to develop, because harvesting fish and vegetables can be done at once and repeatedly. This activity also opens up new job opportunities for the community that can be applied to other yards around Situgede Village.